Digital Library Revolution: Welcoming the Era of AI Robots as Future Knowledge Assistants - Cuikitalia, Cuikitalia; Prayitno, Heri; Gusra, Dedi (Brawijaya University Library, 2024)
Introduction: Artificial intelligence (AI) technology has permeated various sectors, including libraries. While AI robots have been extensively studied in many fields, research on their application in libraries remains limited. This study explores the potential, challenges, and impact of AI robot integration in future libraries. Methods: A systematic literature review (SLR) was conducted using the Scopus database. Content analysis was applied to identify the use, challenges, and impact of AI robot integration in libraries, including current technologies and future projections. Results: From 592 initial articles, 21 were selected for data extraction after screening and quality assessment. The research reveals AI robots' potential to enhance service efficiency, personalization, and user experience while promoting innovation in libraries. Implementation challenges include technical, social, economic, legal, ethical, educational, and environmental aspects. Impacts include improved services, operational efficiency, and transformed staff roles. Discussion: AI robot integration in future libraries focuses on enhancing customer service, collection management, and security. Major challenges lie in educational, social, legal, and ethical domains. While significant impacts on service quality and efficiency are expected, changes in user experience and overall operations may be less dramatic. Conclusion: AI robot integration in libraries has the potential to significantly improve services and efficiency. While technical challenges can be addressed, social and legal aspects require careful consideration. A balanced approach to AI implementation is necessary to maximize benefits while minimizing disruption in the library environment.